A Way from Renewable Energy Sources to Urban Sustainable Development: Empirical Evidences from Taichung City - Hong, Cheng-Yih; Yen, Yu-Shuang (International Journal of Energy Economics and Policy, 2019)
Taiwan pursues economic growth, but the environment also faces major threats. How to balance economic growth and environmental maintenance has become a priority for sustainable development. This study analyzes this issue from a regional perspective. Taichung City is a scaled-down version of Taiwan's economic development. This case study will help to think about how the economy and the environment can achieve a win-win situation in the future. This study analyzes the economic effects of investments in solar systems and then analyzes the differences in CO2 emissions between electricity consumption and electricity sources. As a source of electricity needed to provide economic activities in Taichung, solar power systems will avoid the large-scale CO2 emissions generated by economic growth and achieve a win-win goal of economic growth and environmental maintenance, which will help to achieve the possibility of sustainable urban development. Keywords: Solar power, Investment, Economic growth, CO2 emissions, Sustainable urban development. JEL Classifications: C67, Q01, Q58, R58 DOI: https://doi.org/10.32479/ijeep.7225